How Work Productivity can Increase at ZAP Clinic Head Office Jakarta - Yosandi Yulius (Journal of Accounting and Finance Management, 2021)
The purpose of this research is to determine (1) the influence of the leadership of the head of ZAP CLINIC Jakarta Headquarters on the work productivity of employees at ZAP CLINIC Jakarta Head Office; (2) The Influence of Employee Discipline on Work Productivity of ZAP CLINIC Employees, Jakarta Head Office; And (3) The Influence of Leadership and Employee Discipline on Work Productivity of ZAP CLINIC Employees, Jakarta Head Office. The research method used is a descriptive survey method and an explanatory survey using a sample of 50 employees of ZAP CLINIC Jakarta Head Office as respondents. Based on the results of the study, it was found that the leadership at ZAP CLINIC Jakarta Headquarters is generally good, but there are several things that need to be considered, namely the lack of smooth communication between employees and leaders, a less conducive work atmosphere, less attention to the situation of employees and uncertainty. Task Structure; Employee Discipline is considered good enough, but discipline needs to be improved, namely punctuality in attendance, obedience in following SOPs, and responsibility in maintaining work infrastructure; Leadership Affects Employee Work Productivity, Where Better Leadership Will Lead to Better Employee Productivity At ZAP CLINIC KA Jakarta Head Office; Discipline Affects Employee Work Productivity, So The Higher Employee Discipline, The Higher Work Productivity; And Leadership And Employee Discipline Together Affect Employee Work Productivity, But When Seen Partially, Leadership Is More Dominant In Affecting Employee Work Productivity Than Employee Discipline.